Education of Young Generation in the Spirit of Patriotism - Yusupov Arabboy Bahodirjon ogli; Mamadaliyev Hasanbek Akmal oglu; Mamadaliyev Husanbek Akmal oglu; Abdujabborov Islamali Umidjon oglu (Zien Journals, 2022)
This article briefly describes the opportunities and foreign experiences that are being created for young people today, the extent to which they fit into our mentality and how we use them to be more scientifically beneficial to young people.
Keywords: Patriotism; multiplicity; USA; central ideas